2003
DOI: 10.1542/peds.112.6.1338
|View full text |Cite
|
Sign up to set email alerts
|

Not Only a Matter of Epilepsy: Early Problems of Cognition and Behavior in Children With “Epilepsy Only”—A Prospective, Longitudinal, Controlled Study Starting at Diagnosis

Abstract: Already in the earliest stage of the illness, children with epilepsy are liable to vicissitudes in cognitive and behavioral functioning. Contextual variables are all-important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
210
0
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(240 citation statements)
references
References 15 publications
14
210
0
16
Order By: Relevance
“…In children with uncomplicated epilepsy, there is also ample evidence demonstrating an increased level of subtle cognitive as well as psychiatric and behavioral problems relative to healthy controls, which could also influence adult outcomes. [8][9][10][11][12][13] The respective impacts of seizure course versus learning and psychiatric problems on adult outcomes have not been distinguished. Understanding what places a child with epilepsy at risk for poorer outcomes in adulthood might contribute to management of childhood epilepsy, determining the need for early educational and psychiatric/psychological services, and planning pediatric to adult transition and transfer of care.…”
mentioning
confidence: 99%
“…In children with uncomplicated epilepsy, there is also ample evidence demonstrating an increased level of subtle cognitive as well as psychiatric and behavioral problems relative to healthy controls, which could also influence adult outcomes. [8][9][10][11][12][13] The respective impacts of seizure course versus learning and psychiatric problems on adult outcomes have not been distinguished. Understanding what places a child with epilepsy at risk for poorer outcomes in adulthood might contribute to management of childhood epilepsy, determining the need for early educational and psychiatric/psychological services, and planning pediatric to adult transition and transfer of care.…”
mentioning
confidence: 99%
“…De modo semelhante, em outro estudo que incluiu 173 crianças com epilepsia crônica, foi documentado um pior desempenho em medidas neuropsicológicas da atenção e da velocidade de processamento na casuística de epilépticos 46 . Oostrom et al 47 , contrariando estudos anteriores, usaram uma extensa bateria de testes neuropsicológicos e perceberam que crianças com epilepsia recém-diagnosticada e crises não complicadas apresentavam mais problemas na avaliação neuropsicológica que o grupo de controle. Entretanto, seus problemas relacionados à atenção eram, em geral, transitórios e não apresentavam relação direta com fatores relativos às crises.…”
Section: ) Problemas Atencionais Na Epilepsia Permitem O Diagnósticounclassified
“…Os erros mais frequentes foram em testes de flexibilidade cognitiva e atenção sustentada. Os pacientes com dificuldades escolares prévias ao início da epilepsia e aqueles cujos pais reagiram de forma menos adaptada ao diagnóstico tiveram um pior desempenho, de forma que os autores concluíram que variáveis relacionadas à epilepsia não justificavam os achados 47 .…”
Section: ) Problemas Atencionais Na Epilepsia Permitem O Diagnósticounclassified
“…Williams et al (19) found no differences in performance on cognitive measures between children with new-onset seizures before and after six months of treatment with AEDs compared to children with recently diagnosed diabetes mellitus. Increased seizure frequency has been negatively related to performance in some studies (7,(23)(24)(25)(26), although other studies found that seizure variables were not strongly related to academic achievement (2,4,14,27).To more clearly define the etiology and natural history of academic difficulties, longitudinal studies beginning early in the course of the seizure disorder are needed. To date, only four studies have examined academic problems among children with new-onset seizures, and in two of the studies (4,14) data on children with both new-onset and chronic seizures were combined and not reported separately.…”
mentioning
confidence: 99%
“…They did not obtain specific measures of each child's academic performance. The final study by Oostrom and colleagues (27,29) compared children enrolled in regular school classrooms who had experienced two or more unprovoked idiopathic or cryptogenic seizures within the past year with gender-matched classmate normal controls. They found that children with epilepsy scored significantly worse on academic skills (reading, writing, and math) than controls and, over the year following entry into the study, a decline in these skills was found.…”
mentioning
confidence: 99%